Study of Mortality Due to Thoraco-Abdominal Injuries in Road Traffic Accidents in Mangalore City (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: After the strict implementation of helmet rule the number of head injuries due to road trafficaccidents has subsequently decreased, but injuries sustained to thoracic and abdominal regions are stillon the rise. This post mortem study of profile of thoraco-abdominal injuries, type, pattern and nature ofexternal and internal injuries involved will be an attempt to highlight the trends of mortality due to thoracoabdominal injuries associated with road accidents in Mangalore city. Material and Methods: Present studywas autopsy record based retrospective study conducted deaths associated with thoracic-abdominal injuriesthat have definite history of road traffic accidents. Results: From 247 deaths of RTA victims who sustainedthoraco-abdominal injuries, most common age group was 20 – 29 (21.8%) years, male: female ratio was 5.6:1. 21 % of cases were spot dead or dead on arrival to hospital, 60 % of cases died within 24 hours. 68.8%cases had thoracic trauma with signs of external injuries such as abrasions (60.7%), contusion (10.5%) andlaceration (10.2%). External abdominal injuries were present on 54.2% cases, 48.9% cases had abrasionfollowed by contusion in 8.9% cases and laceration in 6.5% cases. 199 (80.6%) cases sustained internalinjuries to thorax. Fractures of ribs were present on 59.5% cases. Injuries to lungs sustained in 37.2% casesand to heart in 22.6% cases. 136 (55.1%) cases of internal abdominal injuries, most common organ injuredwas liver (38%), followed by spleen (17%) & abdominal wall (14%). Among the 247 cases, cause of deathin 47% cases was head injury followed by thoraco-abdominal injury (20%), head injury and thoracic injury(8%), only thoracic injury (7%), abdominal injury (6%). Conclusion: The present study maximum numbersof the victims were males, from age group of 20-39 years, reported on city roads, pedestrians, noted insummer season and cause of death was head injury followed by thoraco-abdominal injuries.
Keywords: mortality, fatal thoraco-abdominal injuries, road traffic accidents, road safety